2021
DOI: 10.3390/cancers13184620
|View full text |Cite
|
Sign up to set email alerts
|

Improving Biologics’ Effectiveness in Clinical Oncology: From the Combination of Two Monoclonal Antibodies to Oligoclonal Antibody Mixtures

Abstract: Monoclonal antibodies have revolutionized the treatment of many diseases, but their clinical efficacy remains limited in some other cases. Pre-clinical and clinical trials have shown that combinations of antibodies that bind to the same target (homo-combinations) or to different targets (hetero-combinations) to mimic the polyclonal humoral immune response improve their therapeutic effects in cancer. The approval of the trastuzumab/pertuzumab combination for breast cancer and then of the ipilimumab/nivolumab co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 102 publications
0
15
0
Order By: Relevance
“…Combinations of passive therapies targeting HER1 and HER2 oncogenes have arisen as an attractive alternative in cancer immunotherapy, proving to be effective in controlling tumor burden ( 21 ) and preventing the development of resistance to TKI and MAbs ( 40 , 42 ). Additional studies have suggested that mixtures of antibodies targeting non-overlapping epitopes are more efficient than single antibodies in inducing HER receptors’ downregulation ( 43 ) and inhibiting tumor progression ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combinations of passive therapies targeting HER1 and HER2 oncogenes have arisen as an attractive alternative in cancer immunotherapy, proving to be effective in controlling tumor burden ( 21 ) and preventing the development of resistance to TKI and MAbs ( 40 , 42 ). Additional studies have suggested that mixtures of antibodies targeting non-overlapping epitopes are more efficient than single antibodies in inducing HER receptors’ downregulation ( 43 ) and inhibiting tumor progression ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, MAbs-induced downregulation of the targets is counteracted by endosomal escape and recycling following endocytosis. In this regard, oligoclonal antibody cocktails have been developed to mimic polyclonal antibodies’ (PAbs) response (as induced by infection or vaccination) and to improve their therapeutic effects ( 21 ). However, this approach has the drawbacks of enhanced toxicity and limited polyclonality, which could be heightened by cancer vaccines that are characterized by a remarkable safety profile ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…The second approach to manufacturing antibody cocktails is to co-express and simultaneously purify all mAbs as a mixture. 21,36 This approach could be susceptible to more manufacturing difficulties related to the purification and analytical characterization of the drug substance, but it becomes feasible when the antibody mixture contains many mAbs. This is the case of rozrolimupab (Symphogen), an antibody cocktail containing 25 unique mAbs produced by co-expression from a mixture of 25 CHO cell lines each expressing one of the antibodies.…”
Section: Manufacturing Approachesmentioning
confidence: 99%
“…For example, each mAb from a therapeutic combination can be formulated in an individual dosage form, and the individual mAbs can be mixed together prior to administration. 21 The co-administration of antibodies has to be distinguished from the sequential administration that is used in combination therapies. 21 In the sequential administration, the first mAb is administered alone, followed by the second mAb, followed by the third mAb, etc., while in co-administration the mAbs are combined directly before administration; for example, by mixing them in the same infusion bag.…”
Section: Co-formulation Versus Co-administrationmentioning
confidence: 99%
See 1 more Smart Citation